A botanical, ecological and hydrological contribution to understanding the Lower River Murray and beyond. Issue 2 (3rd July 2017) - Nicol, Jason M.; Ganf, George G.
ABSTRACT: This paper summarises Keith Walker's contribution to the understanding of aquatic, littoral and floodplain understorey vegetation in inland arid, semi-arid and Mediterranean aquatic ecosystems. The work undertaken by Keith and his Ph.D. students included the vegetation dynamics of lower River Murray weir pools, wetlands and floodplains, Darling River floodplain lakes and adaptations of plants to these environments. Studies showed that hydrology was the primary driver of the vegetation of these systems and changes to hydrology brought about by abstraction and river regulation resulted in changes to floristic composition. The responses and investigations of adaptions of individual species to hydrology in controlled experiments provided information regarding the mechanisms of change brought about by altered hydrology. This information has provided the basis of our understanding of vegetation dynamics in weir pools, fundamentally changed how weirs and storages were operated in the lower River Murray, contributed to guidelines for the management of wetlands with flow control structures and the development of vegetation monitoring programs used to assess the effectiveness of restoration activities.